Putting pen to screen on Tablet PCs. - Wolfe, A. (IEEE spectrum)
With the release of the first Tablet PCs produced to Microsoft Corp.'s general specifications, handheld computers may be about to leap into the ring with today's laptops. They will be about the size of the smaller laptops, will be at least as powerful, and maybe their biggest selling point-will be able to handle handwritten text. The Tablet PCs will be amply configured, general-purpose machines with more than enough power to run the full-blown Windows XP operating system. In particular, they will allow handwritten text to be entered onto a digitizing tablet and recognized, a functionality that's called pen-based computing. The Tablet PC will far outpace the computing power of existing small devices such as PDAs (personal digital assistants), including those variants based on Microsoft's own Pocket PC operating system.